LAPORAN KEUANGAN BERBASIS STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL DAN MENENGAH BAGI PELAKU USAHA MIKRO - Ati Harianti; Ludwina Harahap; Hendyansyah Hendyansyah (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2020)
Abstract- Financial statements are a source of financial information for the entity measuring the performance. The financial statements are prepared in certain accounting standards (SAK); General IFRS-based, ETAP or EMKM, according to business size classification. For small and micro businesses (SME’s), based on SAK EMKM. The standards have been modified several times. Simplification is carried out to make it easier for micro and small entities to prepare financial reports based on standards, however, in fact, is that SMEs mostly do not make business financial reports with or without accounting standard. The standard is still considered to be too difficult for micro and small entities. This research was conducted to determine the perceptions of micro-businesses in preparing financial statements based on SAK EMKM. By using primary data and the results of small focus group discussions, as well as testing using Structural Equation Modeling, there are 2 factors that significantly influence the perceptions of SMEs in making financial reports, those are the benefits of the Financial Statements and the timing of the preparation of Financial Statements. The SME’s know the benefits/advantages of preparing Financial Statements, while the challenges faced are the lack of knowledge about accounting records and the lack of sufficient time to make financial reporting.